Asyik Cantik Attire / Munira Za'aba - Za'aba, Munira (2021)
Asyik Cantik Attire is the business of ‘Baju Kurung’ in which that I am involved. My business is located in Semenyih Selangor. because, as we know, Semenyih is a place with a large population and also many facilities that make many customers who can come from various places such as in Bangi, Putrajaya, Kajang and many more. Asyik Cantik Attire has released a baju kurung product called Adeena Kurung. These Adeena Kurung are available in various sizes from XS to XXL and have a variety of attractive colors to be styled by the wearer. High quality fabric made from Como crepe will make the wearer feel comfortable to wear baju kurung from Asyik Cantik Attire. In order for me to achieve the success in Asyik Cantik Attire’s business, I would like to highlight a few components of strength and also analyze the systematic planning. one of which is by promoting sales products on the social site "Facebook". When this business is promoted on Facebook, indirectly, it will increase sales. With sales using the Hard Sell and Soft Sell methods, customers will be easily attracted to the way we present and will buy the products that have been displayed. In addition, displaying a 'teaser' before selling the product will make customers interested in the product to be sell. This will cause customers to follow up and like our pages on the social site “Facebook” to find out what items will be selling. Asyik Cantik Attire juga is also recognized by commitment to providing high-quality products, not only in terms of product, but also by providing polite and respectful and high-quality service.